KEUNGGULAN KOMPARATIF DAN KOMPETITIF USAHA AGRIBISNIS AYAM RAS PEDAGING DI KABUPATEN LAMONGAN JAWA TIMUR - NOVI ITSNA HIDAYATI (Fakultas Pertanian Universitas Yudharta Pasuruan, 2011)
ABSTRACT: The aim of research are: (1) Analyze comparative and competitive adventage of the broiler agribusiness industry at the Regenzy of Lamongan, East Java (2) Analyze avian influenza impact regarding to broiler agribusiness industry at the Regenzy of Lamongan, East Java. Research location in selected by purposive sampling method with concideration that the Regency of Lamongan is one of central production which is nearby with main market, Surabaya, and also obviously the one of positively infected. The research result shows the performance of broiler agribusiness industry at the Regency of Lamongan still not really good, based on IP value is 240 or less than 270 financial and economic income of broiler agribusiness industry at the Regency of Lamongan, before and after infected to eny scala of industry has positive value, ir means broiler agribusiness industry made financial profit for breeder and give economic adventage for the people, broiler agribusiness industry at the Regency of Lamongan entirely has comparative and competitive adventage showed by DRCR value less than 1.